(untitled) (GIST – Education and Learning Research Journal, 2016)
Several experimental studies have examined the effect of the use of mobile applications on improving language skills, but little research has explored the impact of using these applications in EFL speaking classes on alleviating foreign language speaking anxiety (FLSA). This study examines the effect of using WhatsApp activities in undergraduate level EFL speaking classes on students’ speaking anxiety, and their feelings about the activities conducted. Thirty-nine undergraduate level participants carried out the tasks on WhatsApp in EFL speaking courses for four weeks. The FLCAS was administered at the beginning and end of the study. Participants’ views about the mobile application activities were also examined through face-to-face interviews. Results showed that WhatsApp experiences significantly impacted the students’ language acquisition by lowering EFL speaking anxiety.